SC-FDMA LTE Performance Through High Altitude Platforms Communications Channel - Iskandar Iskandar; D. Hidayat (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2016)
It is known that HAPS is one of the promising wireless infrastructures in the years to come. HAPS exploit many advantages from cellular satellite system as well as from cellular terrestrial system. Therefore, HAPS is envisaged as a novel technology for communication. This paper aims at evaluating the performance of a pilot-based channel estimation for uplink LTE using SC-FDMA over Ricean HAPS communication channel. Pilot-based channel estimation is used to estimate an uplink channel of LTE users who transmit the data to HAPS as a base transceiver station (BTS). Analysis is performed to determine the effect of users elevation angle with respect to user position inside HAPS coverage, LTE channel bandwidth, modulation type, and the Doppler frequency shift effect. We found that user’s elevation angle contribute major effect to the pilot-based channel estimation of LTE SC-FDMA performance. System capability to overcome fading effect that users with low elevation angle would be needed to increase the performance. In particular to keep an acceptable performance, in this paper we compensate the channel bandwidth, changing modulation type, and limit the Doppler effect through vehicle speed limitation.